(untitled) (Configurazioni. Research on contemporary poetry, 2022)
Among different species of poetry-forms, an outstanding role is played, in the XX century, by what different languages call poema extenso, long poem, poemetto, langes Gedicht. It is well known that Edgar Allan Poe blamed such a kind of poem, but despite the contemporary prevalence of lyric poetry and its short forms, many poets did not disdain to practice the long ones and to articulate their discourse in very different modes, whether narrative or dramatic, expanding their verses towards complex measures and structures. A comparative approach to the problem will contribute to design a typology of the phenomenon, and to reveal the many ways used by poets to open up the lyric cage.